RELAÇÃO ENTRE ESTRESSE OXIDATIVO E DEPRESSÃO EM MULHERES IDOSAS DA CIDADE DE SANTA MARIA/RS - Machado, Laura Morais (2019)
Introduction: Depression is a serious, complex pathology and represents a serious public health problem. Major Depressive Disorder (MDD) is the most prevalent pathology in the group of depressive disorders.Depressive episodes in the elderly are increasingly common and are associated with higher health costs, premature mortality rates, and comorbidities with typical aging pathologies. Several studies have been carried out over the years to better understand the pathophysiology of depression and it has recently been demonstrated that oxidative stress is one of the possible mediators pathogenic to the disorder. Many of the risk factors for MDD cause changes in markers of oxidative stress. Objective: to identify the relationship between depression and oxidative stress in elderly women in Santa Maria, RS. Methodology: a descriptive cross-sectional study was carried out with elderly women from the city of Santa Maria (RS, Brazil). A total of 47 women with a mean age of 67 years participated in the study. Blood samples were collected for the laboratory dosages of oxidative stress markers and biochemical analyzes. After the samples were collected, the following instruments were applied: sociodemographic data questionnaire, Mini Mental State Examination and Hamilton Depression Scale. The activity of oxidative stress was evaluated by the determination of catalase enzymes, NPSH and the Thiobarbituric Acid Reactive Substances (TBARS) method. Results: the majority of the participants were overweight and BMI on average 29.2. The prevalence of depressive symptoms in the population studied was 55.3%. TBARS had a positive correlation with Hamilton scale scores for depression. Women with depressive symptoms had higher TBARS than non-depressive women. Positive associations were also identified among the sociodemographic variables of schooling, marital status, income and with WHOm they reside. Conclusion: this study found a positive association between markers of oxidative stress and depressive symptomatology in elderly women in the city of Santa Maria RS. The results suggest that oxidative stress is a possible pathogenic mediator of depressive symptomatology, but the direct relationship between the two variables needs to be better elucidated.